ANALYSING STUDENTS’ DIFFICULTIES IN THE LEARNING PROCESS OF WRITING DESCRIPTIVE TEXT - Repianti Suniaderi; Aseptiana Parmawati (IKIP Siliwangi, 2022)
Writing is one way to communicate in written form to convey a message. Descriptive text is on of the learning topics for seventh grade students of SMPN SATAP Rimbakarya. The purpose of this study is to analyze students’ difficulties in the process of learning to write descriptive texts. This research uses descriptive qualitative research methods. The research subjects were 20 students of seventh grade. The results revealed that students opposed several problems in learning interest and motivation then linguistic aspects. Keywords: Students’ Difficulties, Learning Process, Writing Descriptive Text